Model Pendidikan dalam Tasawuf - Yusno Abdullah Otta (Journal of Islamic Education Policy, 2017)
ABSTRACT This study shows that education in Sufism has its own uniqueness compared to the model of education in general. The uniqueness is evident from their educationnal designs and models that apply distinctive patterns and stages, known as soul cleansing. The process pursued in Sufism education model is necessary, given that the material and practise that are lived and practiced are not always concrete and physical. The majority of the material is metaphysical, so that a special educational media is required. For the Sufis, education is not only the media to gain ‘learned knowledge’, that is hushuli, but also the presented knowledge, that is hudhuri. The latter type of knowledge is difficult for a man to gain if he or she relies only on the power of reason and senses. There is no suitable medium for acquiring this type of knoweledge except the purification of the soul and heart through the consistency in guarding of its fitrah consciousness. The form of awareness of nature that opens the opportunity to open the veil/curtain of separation between the self with the object and reality. To be able to maintain the state of awareness of nature in perfect state there is no other way except with the purification of the soul through soul management that is not easy.Keywords: Education, radikalisme, tasawuf